Main Problems of Protection of Shareholder’s Rights in Georgia - Jinoria, Khatuna (European Scientific Journal, ESJ, 2017)
The development of market and fair competition is based on the protection of individuals’ rights including shareholders’ rights. The interests of investors are ensured by solid legal guarantee. It is however important to keep in mind that the important goal of drawing the attention of investors should not jeopardize the rights of minority shareholders. Shareholders’ rights drew the attention of scholars from the very beginning. Despite the efforts of numerous authors, development of case-law and several legal reforms, the way to solve the difficulty that arose due to contradiction between the interests of those two groups – minority and majority shareholders – is still missing. After “velvet revolution”, in an attempt to create an attractive environment for foreign investors, Georgian legislators went overboard and broke the balance at minority shareholders stake. It is very important to finally find the right balance to protect both groups and also to ensure the normal functioning of the company. The article is focused on the identification of the main problems of the protection of shareholders’ rights in Georgian legislation and court practice. It overviews the legal model of regulation and outlines the directions of the necessary legislative reforms. The deficiencies that violate minority shareholders’ rights on legislation level by setting unclear and unbalanced procedures were sorted out. The article also offers general directions of legal amendments which are necessary to eliminate flaws in Georgian legislation and court practices.